ANALISIS PENGARUH TANGIBLES, REABILITY, RESPONSIVE, ASSURANCE, DAN EMPHATY TERHADAP KEPUASAN PELANGGAN PADA TOKO CITRA ELEKTRONIK - Talia; Astuti, Nelly; Tigor, Rian Hasianda (Jurnal Progresif Manajemen Bisnis, 2023)
This is an undergraduate thesis was written by Talia, with student 640180083, major in Management, entitled "Analisis Pengaruh Tangibles, Reability, Responsive, Assurance, dan Emphaty terhadap Kepuasan Pelanggan pada Toko Citra Elektronik”. The results of the study show that the application of leadership style has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performance. Work discipline has a partial and significant positive effect on employee performance. Simultaneously positive and significant effect between leadership style, motivation, work discipline on employee performance with a value of 182,362 ftable 3.16.